X Netizens' Response to the Wayan Mirna Salihin Case after the Ice Cold Documentary Film was Released in George Gerbner's Model of Mass Communication - Pradika, Mohammad Fawaid (Kalijaga Journal of Communication, 2023)
This research tries to analyze netizen Mirna Salihin's case's viral response in the mass media in 2016, and the whole public was talking about it. The case became popular again after the murder documentary was released on Netflix and sparked various discussions on social media. Netizens tried to find out what was considered odd about the murder. This research uses a qualitative descriptive method with netnographic analysis to explore social media phenomena. In this research, individuals or accounts on social media have the same capabilities as mass media. Individuals can summarize an event and choose which message (M1) will be shared with those closest to them or the public. The event summary is then spread to other individuals, triggering other opinions and being able to use the message (M1) to create other messages (M2), and so on. This research shows that the X Tirto.id account is a Man or Machine (M) who sees events and makes selections, then presents his views via social media, resulting in responses from other users such as the Bro Win and Ridwansyah Putra (E3) accounts as individuals who reinterpreted the Mirna Salihin case until other users responded again.